Relative extent of adenobypopbyseal tissue in buffalo hypophysis cerebri - KHAN, MASSARAT; SAIGAL, RAJYA PAL (The Indian Journal of Animal Sciences, 2013)
Hypophyses cerebri of 4 male buffalo calves and 8 adult female buffaloes were studied. The shape of the gland and the relative extent of its different lobes, as varied with age, were illustrated. The extent of adenohypophyseal tissues in relation to neurohypophysis was significantly different from that of cattle. The adenohypophyseal tissues increased with age to expand from the lateral aspect onto the dorsal aspect of the gland. The neurohypophysis extended caudally much beyond the pars distalis and was covered with a thin layer of distalis, and was covered with a thin layer of pars intermedia tissue all around except sometimes at its caudal end.